Pengaruh Pijat Oksitosin Terhadap Pengeluaran ASI Pada Ibu Post Partum Primipara Di RSIA Srikandi IBI - Kholisotin, Kholisotin; Munir, Zainal; Astutik, Lina Yulia (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2019)
Mother's milk (ASI) is the first and best food that must be given to babies because it contains nutrients that are needed in the process of growth and development of children's intelligence. One of the causes of failure to support breast milk has not been released from breast milk after the mother receives it. Expenditures of breast milk can be accelerated by non-pharmacological actions, namely through oxytocin massage which can be done by massaging the area around the back (vertebra pars thoratica) to stimulate the release of breast milk. Objective: This study aimed to determine the effect of oxytocin massage on the release of breast milk in primipara postpartum mothers at RSIA Srikandi IBI. Method: this study is a pre-experimental study with a static group comparison design: randomized control group only design, the number of respondents in this study were 36 consisting of 18 experimental groups and 18 control groups. Results: this study used a paired t-test t test obtained P = 0.001 (P <0.05). Keywords : Oxytocin Massage, Primiparous Post Partum M/other